Research Note Heroes, Historians, and the New Propaganda Movement, 1950-1953 - Ileto, Reynaldo C. (Philippine Studies: Historical and Ethnographic Viewpoints, 2010)
The work of John Schumacher, S. J.,prompts reflection on the attempt to foment a new Propaganda Movement inthe early 1950s. Various individuals and social movements vied for influence or control over the state and nation-building process by connecting their present to the late-nineteenth century. Discourses on heroes and an "unfinished revolution" were deployed to maintain a momentum of change inthe wake of the defeat of the communist-led Huk rebellion. Two key actors of this period were Jose Lansang and Fr.Horacio de la Costa, S.J. Lansang, who served as speechwriter of Pres. Elpidio Quirino, rejected armed struggle, sought to instill national pride through the study of history, and evoked a hew Propaganda Movement. De la Costa perceived a power vacuum with decolonization and strategized for the Catholic Church to "go to the masses" to prevent a communist success. Lansang's group and the church would coalesce in supporting Magsaysay for the presidency in1953.